THE INFLUENCE OF PUBLIC LEADERSHIP ON THE LEVEL OF PUBLIC TRUST IN THE CITY OF MEDAN - Artha Lumbantobing (The American Journal of Interdisciplinary Innovations and Research, 2024)
The problem formulation that emerges from this research is how the variables of servant leadership and innovative leadership influence the trust of the people of Medan City through increasing leader commitment as an intervening variable . The subjects of this research are employees at Medan City Hall, where the variables in this research are the independent variables, namely servant leadership and innovative leadership , the dependent variable, namely the trust variable of the people of Medan City and the intervening variable is the variable for increasing leader commitment . The results of data analysis used SEM analysis using SMART PLS 3.0 software. as for data collection techniques using questionnaires and observational studies . Method research using descriptive quantitative data analysis methods using the structural equation model (SEM) method, where the results of data processing using the SEM method are carried out using the PLS 4.0 application . From the results of this research, the conclusion that exists is that partially only the innovative leadership variable has an effect on increasing public trust and has an effect on leader commitment. Simultaneously, the variables of servant leadership and innovative leadership influence increasing public trust through the variable of leader commitment as an intervening variable . The more there is a culture of service and high innovation, it will actually increase the leader's commitment to always implementing a culture of service and being able to be creative in overcoming problems experienced by society, as well as eliminating the bureaucratic system and making flexible the existing work culture by leaving the bureaucratic work culture and finding a culture work that is able to respond to all community complaints naturally.